Readings in Russian poetics formalist and structuralist views - Matejka, Ladislav 1919-2012; Pomorska, Krystyna (Michigan Slavic contributions, 1978)
A collection of the most important contributions concerning the Formalist school, most of them translated for the first time from the Russian or the Czech.